Position of 24-hour ambulatory blood pressure monitoring in modern practice - V. M. Gorbunov (Кардиоваскулярная терапия и профилактика)
Currently, 24-hour ambulatory blood pressure (BP) monitoring (ABPM) is the gold standard for diagnosing hypertension (HTN) and evaluating the effectiveness of antihypertensive therapy. The method provides information about some BP parameters that cannot be obtained in any other way. ABPM is reasonable in any patient with a documented increase in BP, especially if specific BP phenotypes are suspected: white coat HTN and masked HTN. Antihypertensive therapy under the ABPM, on average, is more economical and is not associated with overprescribing of drugs and their combinations. Based on the ABPM data, calculating a number of additional indicators of the 24-hour BP profile is possible, but their scope is still limited to the research field. In the conclusion on ABPM data, the results of office BP measurement and antihypertensive therapy should be indicated.